Can Urinary Catheterization Before Birth Reduce Postpartum Urinary Retention? - Mehmet B. Şentürk; Hakan Güraslan; Ender Güven; Yusuf Çakmak; Mehmet Şükrü Budak (Medical Network, 2016)
Objective: Postpartum urinary retention (PUR) is defined as no spontaneous micturition in a period of more than 6 hours postpartum or residual volume of >150cc after urination. If a diagnosis is not made, there may be problems of over-distention of the bladder and consequently, denervation, detrusor atony and long-term micturition problems. This study aimed to examine the effect of urinary catheterization during birth on postpartum urinary retention (PUR). Study Design: A prospective randomized study was conducted with 137 patients. The study and control groups were formed according to a random number table. In the study group, urinary catheterization was applied before birth. In both groups, the time of the first postpartum micturition was recorded and after the first micturition, the residual urine volume was measured with catheterization. Cases with no spontaneous micturition in the first 6 hours postpartum were accepted as PUR. The two groups were compared with respect to time of first micturition and residual urine volume using Mann Whitney U-test and the presence of PUR with Chi-square test. Results: The time to first micturition was determined to be shorter in the group where urinary catheterization was applied before birth, the PUR rate was lower and the amount of residual urine was less (p<0.05). Birthweight, duration of labour, maternal age, weight, gravida and use of oxytocin were similar between the groups (p>0.05). Conclusion: Urinary catheterization before birth reduces the rate of PUR.